Avoiding Pitfalls in Comparison of Activity and Selectivity of Solid Catalysts for Electrochemical HMF Oxidation. Issue 5 (24th May 2021) - Wöllner, Sebastian; Nowak, Timothy; Zhang, Gui‐Rong; Rockstroh, Nils; Ghanem, Hanadi; Rosiwal, Stefan; Brückner, Angelika; Etzold, Bastian J. M.
Abstract: Electrocatalytic oxidation of 5‐hydroxymethylfurfural (HMF) offers a renewable approach to produce the value‐added platform chemical 2, 5‐furandicarboxylic acid (FDCA). The key for the economic viability of this approach is to develop active and selective electrocatalysts. Nevertheless, a reliable catalyst evaluation protocol is still missing, leading to elusive conclusions on criteria for a high‐performing catalyst. Herein, we demonstrate that besides the catalyst identity, secondary parameters such as materials of conductive substrates for the working electrode, concentration of the supporting electrolyte, and electrolyzer configurations have profound impact on the catalyst performance and thus need to be optimized before assessing the true activity of a catalyst. Moreover, we highlight the importance of those secondary parameters in suppressing side reactions, which has long been overlooked. The protocol is validated by evaluating the performance of free‐standing Cu‐foam, and CuCoO modified with NaPO2 H2 and Ni, which were immobilized on boron‐doped diamond (BDD) electrodes. Recommended practices and figure of merits in carefully evaluating the catalyst performance are proposed. Abstract : Proposal of a measurement protocol for comparison of electrocatalysts for the HMF oxidation with standard evaluation (yield, faradaic efficiency), as well as a new figure of merit (production rate) to compare catalysts independent from setup size. Additionally, the alkaline degradation of HMF is evaluated and taken into account for closing the mass balance in order to assess the true catalyst activity.